A Pharmacokinetic Bioequivalence Study of Fremanezumab Administered Subcutaneously Using an Autoinjector and a Prefilled Syringe. Issue 9 (7th January 2021) - Cherniakov, Irina; Cohen‐Barak, Orit; Tiver, Ryan; Gillespie, Michael; Kessler, Yoel; Gutierrez, Maria; Rasamoelisolo, Michele; Li, Shawn; Shen, Honglue; Hallak, Hussein; Loupe, Pippa S.; Smith, Michael; et al.
Abstract: Fremanezumab (AJOVY; Teva Pharmaceutical Industries Ltd, Netanya, Israel), approved for the preventive treatment of migraine, is available as a subcutaneous injection either once a month or once every 3 months using an autoinjector or a prefilled syringe. The present study evaluated the pharmacokinetic (PK) bioequivalence of a single subcutaneous injection of fremanezumab 225 mg administered using an autoinjector compared to a prefilled syringe in healthy volunteers. Blood samples for PK and antidrug antibodies were collected before and after dosing. Safety and tolerability assessments included physical examinations, adverse event reporting, laboratory evaluations, and immunogenicity. Following single‐dose administration, the mean concentration‐time profiles for the 2 treatment groups (autoinjector, n = 106; and prefilled syringe, n = 110) were similar. The point estimates for the back‐transformed ratio (autoinjector/prefilled syringe) of geometric least squares means of maximum plasma concentration, area under the plasma concentration–time curve from time 0 to the time of the last measurable drug concentration, and area under the plasma concentration–time curve from time 0 extrapolated to infinity were 1.03, 1.04, and 1.05, respectively, with the 90% confidence intervals entirely contained within bioequivalence margins of 0.8 to 1.25. For both groups, median time to maximum observed concentration was 5 days and mean terminal elimination half‐life was approximately 29 days. Treatment‐related adverse events were reported by 39 (36%) subjects in the autoinjector group and 26 (24%) in the prefilled syringe group, and the majority were nonserious injection site reactions. The incidence of treatment‐emergent antidrug antibody response was low and evenly distributed between the autoinjector (n = 3; 3%) and prefilled syringe (n = 4; 4%) groups. These results indicate that the fremanezumab autoinjector presentation provides an easy‐to‐use bioequivalent PK profile with a similar safety and tolerability profile to that of the prefilled syringe.